A National Referral Service for Paediatric Brachytherapy: An Evolving Practice and Outcomes Over 13 Years. Issue 4 (April 2023) - Gaze, M.N.; Smeulders, N.; Ackwerh, R.; Allen, C.; Bal, N.; Boutros, M.; Cho, A.; Eminowicz, G.; Gill, E.; Fittall, M.W.; Humphries, P.D.; Lim, P.; et al.
Abstract: Aims: Most children requiring radiotherapy receive external beam treatment and few have tumours suitable for brachytherapy. No paediatric radiotherapy centre will treat enough patients from its own normal catchment population for expertise in brachytherapy to be developed and sustained. Following discussion and agreement in the national paediatric radiotherapy group, a service for paediatric brachytherapy in the UK has been developed. We report the process that has evolved over more than 10 years, with survival and functional outcome results. Materials and methods: Since 2009, potential patients have been referred to the central paediatric oncology multidisciplinary team meeting, where imaging, pathology and treatment options are discussed. Since 2013, the National Soft Tissue Sarcoma Advisory Panel has also reviewed most patients, with the principal aim of advising on the most suitable primary tumour management for complex patients. Clinical assessment and examination under anaesthetic with biopsies may be undertaken to confirm the appropriateness of brachytherapy, either alone or following conservative surgery. Fractionated high dose rate brachytherapy was delivered to a computed tomography planned volume after implantation of catheters under ultrasound imaging guidance. Since 2019, follow-up has been in a dedicated multidisciplinary clinic. Results: From 2009 to 2021 inclusive, 35 patients (16 female, 19 male, aged 8 months to 17 years 6 months) have been treated. Histology was soft-tissue sarcoma in 33 patients and carcinoma in two. The treated site was pelvic in 31 patients and head and neck in four. With a median follow-up of 5 years, the local control and overall survival rates are 100%. Complications have been few, and functional outcome is good. Conclusion: Brachytherapy is effective for selected paediatric patients, resulting in excellent tumour control and good functional results. It is feasible to deliver paediatric brachytherapy at a single centre within a national referral service. Highlights: A national referral service for paediatric brachytherapy has been established in the UK. Potential patients are carefully selected for suitability through a national multidisciplinary expert panel discussion and clinical evaluation. Over 13 years, 35 patients have been treated with a median follow-up of 5 years. All patients have achieved local control and the 5-year survival probability is 100% with good functional outcomes.